Asymmetrical 1, 3‐Bis(heteroazolyl)benzene Platinum Complexes with Tunable Second‐Order Non‐Linear Optical Properties. Issue 29 (6th September 2016) - Dang, Tung T.; Soulé, Jean‐François; Doucet, Henri; Benmensour, Mohamed Ali; Boucekkine, Abdou; Colombo, Alessia; Dragonetti, Claudia; Righetto, Stefania; Jacquemin, Denis; Boixel, Julien; Guerchais, Véronique
Abstract : A series of cyclometallated platinum(II) complexes bearing an asymmetrical 1, 3‐bis(heteroazolyl)benzene ligand as well as a chloro or phenylacetylene ancillary ligand have been synthesized and characterized. The N^C^N pro‐ligands, (benzoxazolyl)(benzothiazolyl)benzene in complex Pt1 and related compounds, and (benzoxazolyl)(benzimidazolyl)benzene in complex Pt2, were synthesized by a two‐step procedure that includes a Pd‐catalysed C–H bond‐activation reaction. The electronic absorption, luminescence and second‐order non‐linear optical properties of the novel complexes were investigated experimentally and theoretically (TD‐DFT) and compared with those of the known 1, 3‐bis(benzoxazolyl)benzeneplatinum complex, the non‐linear optical response of which has been studied for the first time. All the complexes exhibit green luminescence in dichloromethane solution at room temperature, the nature of the heteroazolyl ligand and/or the substituent on the central phenyl ring having no significant impact on the emission signatures. In contrast, functionalization of the terdentate ligands and the nature of the ancillary ligand (chloride or phenylacetylide) allow modulation of the non‐linear optical activity. Abstract : A new series of cyclometallated platinum(II) complexes bearing an asymmetrical 1, 3‐bis(heteroazolyl)benzene ligand have been prepared. The N^C^N pro‐ligands were synthesized by a two‐step procedure that includes a Pd‐catalysed C–H bond‐activation reaction. All the complexes exhibit green luminescence at room temperature and a strong NLO response that can be tuned by ligand design.